Hubungan Disiplin Kerja Dengan Kinerja Karyawan Pada PT. Varia Intra Finance Cabang Lampung - Kuntum Vuspasari (Jurnal Manajemen dan Bisnis, 2011)
PT. Varia Intra Finance engaged in vehicle leasing KTM Brand Lampung Province facing the problem of low levels of labor discipline and a level of performance. The purpose of this study is to determine whether there is a relationship between the job discipline with employee performance PT. Varia Â Intra Finance Branch Lampung. This research uses descriptive method, Library Research and Field Research, and data collection techniques of observation, interviews, questionnaires, and documentation. This study is a population and employs 31 people as respondents. In conducting the analysis used qualitative and quantitative methods of analysis. Formula used in the quantitative analysis Product Moment Correlation and t- test. Based on the results of the qualitative analysis it can be concluded that the response of employees to work discipline is low. It can be seen from the results that 23% of respondents answering high, 32% moderate, 45% said low. Responses also employee performance in the category of low rate of 19% said the performance was already high, and 29% moderate, and 52% said low. Based on the results of quantitative analysis Product Moment Correlation obtained value of r = 0.802, further consultation with the r-table at n = 31, significant at the 95% level (Î± = 5%) results obtained r-table 0.355, mean-count r> r- table. This means that there is a relationship between the discipline of working with employee performance. To determine the degree of closeness of relationship can be seen table interpretation, r = 0.802 lies between 0.800 to 0.1000, which means having a high influence. From the calculation results obtained by t-value = 7.228 and t-table = 2.048 at n = 31, d = 31-2 = 29 and with a significant level of 95% (Î± = 5%), mean 7.228 t count> t 2.048-table, meaning Ha accepted. This suggests that there is a strong and positive relationship between the disciplines of work and employee performance. Thus the hypothesis that Job Discipline has to do with the performance of the employees of PT. Varia Intra Finance Branch Lampung is acceptable.